Investigation of the bioactive constituents of Goniothalamus wightii: Antioxidant, anti-inflammation, antimicrobial, anticancer, and molecular docking studies (Kuwait Journal of Science)
The aim of the current study was to isolate and purify the bioactive metabolite compound using Goniothalamus wightii leaf extracts and evaluate the antioxidant, antibacterial, antibiofilm, and in vitro cytotoxic activities and their in-silico molecular docking studies. A novel compound of 6-[(E)-2-phenylethenyl]-5,6-dihydro-2H-pyran-2-one was purified by column chromatography and characterized by fourier transform infrared spectroscopy, liquid chromatography-mass spectrum, and types and numbers of nuclei in a molecule are examined by nuclear magnetic resonance. Antioxidant activities are evaluated by 2, 2-diphenyl-1-picyrl-hydrazyl, 2ʼ, -2ʼ azino bis-(3-ethylbenzothiazoline-6-sulphonic acid, and ferric reducing power assays. The antibacterial and antibiofilm activities of active bio compounds against human pathogens by agar well diffusion methods. Cytotoxic activities of the active compound were evaluated against breast and cervical cancer cell lines by cytotoxicity assay and acridine orange/ethidium bromide staining methods. Likewise, anti-inflammatory activities have more potent inhibitory effects on human red blood cell membrane stabilization and protein denaturation assays. Further, this compound was evaluated computationally using Schrödinger software. The antimicrobial, antioxidant, and anticancer protein markers were chosen based on their activity and properties. The discovered bioactive compound synergizes and may lead to new drugs shortly. This study concluded that the 6-[(E)-2-phenylethenyl]-5,6-dihydro-2H-pyran-2-one is a moral source isolated from the natural medicinal plant for therapeutic purposes. © 2025 The Author(s)